MIG – VP: Negative current effect and proportion of electrode negative on the penetration alumínium weld bead - González, Leandro Rubén; González, Arnaldo Ruben; Pimentel, Rafael Ellwanger; Botega, Matheus (Seven Editora, 2024)
The MIG (Metal Inert Gas) process with variable polarity (VP) is a relatively new process that can be applied in the welding process industry with high deposition rates and competitive costs. The process uses curves composed of pulses in positive and negative polarities and presents as main benefits in relation to the conventional process, a high melting rate, combined with low thermal input, smaller deformations, and better control of penetration and dilution. The objective of this work is to analyze the effect of the negative current (In) and the proportion of negative electrode (%EN), of the typical current curve of the variable polarity process, on the penetration of the weld beads. For the study, three levels of In of -70 A, -50 A, and -30 A and four levels of %EN percentages of 20%, 30%, 40%, and 50% were used, applying a fully crossed factorial experiment design. Weld beads were made in the flat position (1G), depositing aluminum ER5356 on the free surface of the Al5052-F sheet. It is suggested that for the negative electrode proportion (%EN), the value of the negative current should be considered, in order to obtain a closer approximation to the effects of In and %EN on penetration. The effect of In on penetration is 13.1%, however, the effect of %EN is 71.6%, also the interaction (In and %EN) is statistically significant contributing with 11.0%. It was concluded that a decrease in negative current in modulus causes a reduction in penetration. Likewise, increasing the proportion of the negative electrode causes a decrease in penetration into the weld bead. DOI:https://doi.org/10.56238/sevened2024.010-050